The Relationship between Financial Technology, Risk Perception, and Regulation on Trust in Digital Financial Services - Supriandi, Supriandi; Supriadi, Adih (West Science Accounting and Finance, 2025)
This study investigates the relationship between financial technology (FinTech), risk perception, and regulation on trust in digital financial services among users in Indonesia. Using a quantitative research design, data were collected from 155 respondents who actively use digital financial platforms such as e-wallets, mobile banking, and peer-to-peer lending. The research employed a Likert-scale questionnaire and analyzed data using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that FinTech has a positive and significant effect on trust, suggesting that technological innovation, ease of use, and transparency enhance user confidence. Conversely, risk perception has a negative and significant effect, showing that security and privacy concerns reduce trust levels. Furthermore, regulation plays a positive moderating role by strengthening the impact of FinTech on trust, implying that effective regulatory oversight enhances institutional credibility and consumer protection. The model explains 68.1% of the variance in trust, reflecting its strong explanatory power. The findings contribute to the theoretical enrichment of the Technology Acceptance Model (TAM) and Institutional Trust Theory, offering practical implications for policymakers and FinTech developers to strengthen public confidence in digital financial ecosystems through innovation, transparency, and adaptive regulation.